La desintegración familiar, en el rendimiento académico de los niños de sexto año de educación básica de la unidad educativa Licto. periodo 2022 - 2023. - Tixi Guallo, Erika Tatiana (2023)
This research was conducted in the facilities of the Licto Educational Unit with the theme of family disintegration in the academic performance of children in the sixth year of basic education, since it is a social problem where the main affected are the children, which causes serious conflicts both inside and outside the home, causing psychological problems of emotional and social order, These types of problems are closely related to the lack of family concern, lack of communication and understanding, resulting in children who have unfavorable attitudes to have a good school performance, resulting in students with poor grades to such an extent that they do not want to continue with their studies. It is for this reason that during this research the structure of the thesis will be detailed, so it was carried out as follows: the first chapter includes the problem, formulation, objectives and justification of the research work, in the second chapter the main theoretical basis of the topic in reference, in the third chapter presents the research methodology in which the methods were applied, scientific analysis and research techniques that were used, namely the survey applied to children of the sixth level in the Licto Educational Unit and the interview with the tutor teacher handled properly for the success of this research. To culminate, conclusions and recommendations were made, the bibliography, the annexes, reaching if to verify that this research was transcendental and important to find the causes and consequences that leads to a child due to family disintegration directly affect their level of academic performance.